APPROXIMATION OF ELECTRIC PROPERTIES OF PERIODIC LAYERED COMPOSITE MATERIALS - Steckiewicz, Adam; Butryło, Bogusław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper presents a discussion on the approximate electrical model of a layered material with the distributed periodic structure of the predefined cells. The macroscopic properties of the material are shaped by the modification of the local geometry of the cell. The proposed SISO model with the polynomial approximation of some selected properties is verified. The algorithm of polynomial approximation is introduced and presented in relation to an exemplary fractal structure. It is also shown the lumped electric model of periodic cell with defined parameters.